Cellular EMT-status governs contact guidance in an electrospun TACS-mimicking in vitro model - Lorenz Isert; Mehak Passi; Benedikt Freystetter; Maximilian Grab; Andreas Roidl; Christoph Müller; Aditi Mehta; Harini G. Sundararaghavan; Stefan Zahler; Olivia M. Merkel (Materials Today Bio)
In this study, an advanced nanofiber breast cancer in vitro model was developed and systematically characterized including physico-chemical, cell-biological and biophysical parameters. Using electrospinning, the architecture of tumor-associated collagen signatures (TACS5 and TACS6) was mimicked. By employing a rotating cylinder or static plate collector set-up, aligned fibers (TACS5-like structures) and randomly orientated fibers (TACS6-like structures) fibers were produced, respectively. The biocompatibility of these fibers was enhanced by collagen coating, ensuring minimal toxicity and improved cell attachment. Various breast cancer cell lines (MCF7, HCC1954, MDA-MB-468, and MDA-MB-231) were cultured on these fibers to assess epithelial-to-mesenchymal transition (EMT) markers, cellular morphology, and migration.Aligned fibers (TACS5) significantly influenced EMT-related changes, promoting cellular alignment, spindle-shaped morphology and a highly migratory phenotype in mesenchymal and hybrid EMT cells (MDA-MB-468, MDA-MB-231). Conversely, epithelial cells (MCF7, HCC1954) showed limited response, but - under growth factor treatment - started to infiltrate the fibrous scaffold and underwent EMT-like changes, particularly on TACS5-mimicks, emphasizing the interplay of topographical cues and EMT induction.The biophysical analysis revealed a clear correlation between cellular EMT status and cell mechanics, with increased EMT correlating to decreased total cellular stiffness. Cancer cell mechanics, however, were found to be dynamic during biochemical and topographical EMT-induction, exceeding initial stiffness by up to 2-fold. These findings highlight the potential of TACS5-like nanofiber scaffolds in modeling the tumor microenvironment and studying cancer cell behavior and mechanics.